Morphological, rheological and in vitro digestibility characteristics of gelatinized starch dispersion under repeated freeze‐thaw cycles. (11th September 2015) - Vernon‐Carter, Eduardo Jaime; Bello‐Pérez, Luis Arturo; Lobato‐Calleros, Consuelo; Hernández‐Jaimes, Carmen; Meraz, Monica; Alvarez‐Ramirez, Jose
Abstract : In this work, the effects of the repeated application of freeze (−20 °C)‐thaw (+90 °C) cycles on the morphology, physicochemical properties and in vitro digestibility of corn starch gels (5% w/w) were studied. The results showed that as the number of freeze‐thaw cycles increased, the compactness of the starch gel also increased. This effect was attributed to a rearrangement of retrograded starch molecules and the disruption of ghosts (i.e., insoluble material), which in turn caused increased syneresis values. Frequency sweeping rheological showed an important increase of the shear stress response (as reflected by increased storage and loss moduli) under small deformations, which was linked to a firmer appearance of the modified starch gel. Compared with the fresh starch gel, the transition temperatures of the modified starch gels in thermal tests markedly increased, while the corresponding endothermic enthalpy decreased. The variation of the infrared absorbance ratio of 1047 cm −1 /1022 cm −1 indicated a decrease of the short‐range order, reflecting increased retrogradation with the application of the freeze‐thaw cycles. Acid hydrolysis and in vitro digestibility indicated that the repeated application of FT cycles increased the resistant starch content as consequence of retrogradation and diffusion effects.